Pengaruh Pendidikan Kewirausahaan Dan Efikasi Diri Terhadap Minat Berwirausaha Siswa-Siswi Kelas XI SMAN 1 Tulungagung Tahun Pelajaran 2021/2022 - Ardeana Kurnia Gusti; Muhammad Anasrulloh (Universitas Hamzanwadi, 2022)
Indonesia faces unemployment and poverty problems, which have an impact on the economy. The right solution is entrepreneurship. The phenomenon of unemployment and poverty in the current era of globalization, the government is trying to foster interest in entrepreneurship in the younger generation. This study aims to determine the effect of entrepreneurship education and self-efficacy of SMAN 1 Tulungagung students on the interest in entrepreneurship. in this study data collection using a questionnaire. The trial consists of a validity test and a reliability test. Prerequisite tests include normality test, linearity test, multicollinearity test and heteroscedasticity. The hypothesis test consists of t test and F test. The data analysis technique uses multiple linear regression. The result of this research is that there is a positive and significant effect on the students' interest in entrepreneurship with a tcount value of 3.744 > 1.993 ttable and a significant 0.000 <0.05. There is a positive and significant influence on the interest in entrepreneurship with tcount 2.875 > 1.993 ttable, and significant 0.000 <0.05. There is a positive and significant effect of entrepreneurship education and self-efficacy on the interest in entrepreneurship as indicated by the Fcount 40.290 > Ftable 3.10. The percentage of the simultaneous influence of entrepreneurship education and self-efficacy on interest in entrepreneurship is 53.2% while the remaining 46.8% is influenced by others outside this study.